Preparation method of fullerol modified carbon fluoride composite material and application of the composite material in lithium primary battery

CN122907626APending Publication Date: 2026-10-13CARBON ATOM (CHENGDU) NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611263162.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-19
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0010]鉴于上述现有技术的不足,本发明的目的在于提供一种富勒醇改性氟化碳复合材料的制备方法及其锂一次电池应用,旨在解决现有技术中氟化碳材料电子导电性差和锂离子扩散动力学缓慢导致的高倍率性能不佳的技术问题,实现提升锂/氟化碳电池能量密度和功率密度的技术效果

Benefits of technology

[0021]有益效果:本发明提供的富勒醇改性氟化碳复合材料中,通过引入特定富勒醇组分,并与氟化碳复合,富勒醇表面的羟基官能团可通过氢键作用锚定在氟化碳表面,实现对氟化碳颗粒的非破坏性表面修饰;这一修饰过程优化了氟化碳片层的堆积结构,拓宽了层间离子传输通道;同时,均匀分布的富勒醇能在氟化碳颗粒之间构建起连续的电子传导通路,从而同步提升了复合材料的电子导电性和锂离子扩散动力学。因此,当该复合材料用作锂一次电池正极时,有效缓解了高倍率放电时的极化现象,使得电池在保持高能量密度的同时,获得了显著提升的功率密度和倍率性能。此外,富勒醇的引入使得复合材料能够良好地适配水系或油系等多种粘结剂体系,有利于简化制备工艺并实现绿色规模化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907626A_ABST
    Figure CN122907626A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of electrochemical energy storage materials, and discloses a preparation method of a fullerol modified carbon fluoride composite material and application of the fullerol modified carbon fluoride composite material in lithium primary batteries, wherein the fullerol modified carbon fluoride composite material comprises carbon fluoride and fullerol, and the fullerol is anchored on the surface of the carbon fluoride through hydrogen bond action. The composite material provided by the application realizes non-destructive surface modification through hydrogen bond action of the surface hydroxyl group of the fullerol and the carbon fluoride, widens an interlayer ion transmission channel and constructs a continuous electron conduction path, synchronously improves electronic conductivity and lithium ion diffusion kinetics, effectively alleviates high-rate discharge polarization when used as a lithium primary battery positive electrode, and significantly improves power density and rate performance while maintaining high energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrochemical energy storage materials technology, and in particular to a method for preparing a fullerol-modified fluorinated carbon composite material and its application in lithium primary batteries. Background Technology

[0002] Lithium / Fluoride (Li / CF) x Primary batteries are among the highest energy density chemical power sources known to date, with a theoretical specific capacity of up to 2180 Wh / kg. They also possess significant advantages such as stable operating voltage, high safety and reliability, low self-discharge rate, long storage life, and environmental friendliness. Based on these superior characteristics, lithium / carbon fluoride primary batteries have irreplaceable application value in high-end special power sources such as aerospace, military equipment, deep-sea exploration, and precision medical devices. Currently, lithium-carbon fluoride batteries with a specific energy of up to 900 Wh / kg can be prepared using high-energy-density fluoride materials, and further optimization is expected to yield ultra-high specific energy primary batteries of 1000 Wh / kg.

[0003] However, the large-scale, high-power application of lithium / carbon fluoride primary batteries still faces significant challenges. CF x As the core positive electrode active material, it has poor electronic conductivity (CF). x (is a wide-bandgap semiconductor), and the interlayer Li + Slow diffusion kinetics. These defects lead to severe electrochemical polarization, significant voltage hysteresis, and a substantial decrease in energy and power density during high-rate discharge, severely limiting their large-scale application in high-power scenarios. Although lithium / carbon fluoride batteries have an extremely high theoretical energy density advantage, the rate performance bottleneck has always been a core challenge restricting their development.

[0004] To address the above issues, several modification techniques have been proposed, mainly including the following categories: (I) Conductive phase composite modification: This method mainly involves modifying CF x Physical mixing or compositing with carbon nanotubes, metal nanoparticles, or conductive polymers can enhance the electronic conductivity of materials. However, these physical compositing methods tend to lead to agglomeration of the conductive phase, weak interfacial bonding, and it is difficult to fundamentally optimize the reactivity of the CF bond and Li bond. + Transport dynamics.

[0005] (II) Chemical Reduction Modification: Some studies have disclosed a technical solution that uses chemical reducing agents (such as hydrazine) to treat fluorinated carbon, thereby improving the electronic conductivity of the material by removing some fluorine atoms. This method utilizes the reducing properties of hydrazine to chemically reduce fluorinated carbon, essentially breaking the CF bonds to achieve surface modification. Although it can effectively reduce the voltage hysteresis of fluorinated carbon and improve its high-rate discharge performance, the chemical reduction process will destroy the intrinsic CF bond structure of fluorinated carbon, leading to a loss of material capacity and energy density.

[0006] (III) High-Temperature Calcination Modification: Some studies have proposed a method of mixing fluorinated carbon with nano-copper and then calcining it at high temperature in an inert atmosphere. The nano-copper reacts on the surface of the fluorinated carbon, improving the voltage hysteresis and high-rate discharge performance of the fluorinated carbon. However, this method involves high-temperature treatment, which can easily cause structural damage and fluorine content loss in the fluorinated carbon, and the process is complex and energy-intensive.

[0007] (iv) Surface coating modification: Existing studies have used polymers to coat the surface of fluorinated carbon particles to improve electrolyte wettability. However, polymer coatings usually have poor electronic conductivity and it is difficult to achieve controllable uniform coating.

[0008] (v) Plasma modification: Some studies have disclosed methods for modifying fluorinated carbon by generating nitrogen and hydrogen plasma using inductively coupled plasma. This method involves complex equipment, high cost, and also carries the risk of damaging CF bonds.

[0009] In summary, existing fluorinated carbon modification technologies generally suffer from the following shortcomings: physical composite methods result in weak bonding between the conductive phase and the matrix interface, leading to limited modification effects; chemical or thermal treatment methods can destroy the intrinsic CF bond structure of fluorinated carbon, sacrificing energy density; most modification methods involve complex processes and demanding conditions, making large-scale production difficult; and it is difficult to simultaneously optimize electronic conductivity and ion diffusion kinetics. Summary of the Invention

[0010] In view of the shortcomings of the prior art, the purpose of this invention is to provide a method for preparing fullerol-modified fluorinated carbon composite material and its application in lithium primary batteries, aiming to solve the technical problems of poor high-rate performance caused by poor electronic conductivity of fluorinated carbon materials and slow lithium-ion diffusion kinetics in the prior art, and to achieve the technical effect of improving the energy density and power density of lithium / fluorinated carbon batteries.

[0011] The technical solution of the present invention is as follows: A fullerol-modified fluorocarbon composite material, comprising fluorocarbon and fullerol, wherein the fullerol is anchored to the surface of the fluorocarbon via hydrogen bonding.

[0012] The fullerol-modified fluorocarbon composite material, wherein the mass of the fullerol accounts for 0.1wt%-10wt% of the total mass of the fullerol-modified fluorocarbon composite material.

[0013] The fullerol-modified fluorinated carbon composite material, wherein the fluorinated carbon includes any one or more combinations of fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, fluorinated carbon fibers, fluorinated Ketjen black, and fluorinated acetylene black.

[0014] The fullerol-modified fluorinated carbon composite material, wherein the fullerol has the molecular formula C60(OH). n Where n is an integer from 16 to 40; the molecular formula of the fluorinated carbon is CF. x , where x = 0.5 - 1.2.

[0015] A method for preparing fullerol-modified fluorinated carbon composite material as described in this invention, comprising the steps of: Fullerol is dispersed in an organic solvent to form a fullerol dispersion; Fluorinated carbon powder is added to the fullerol dispersion, and the fullerol is uniformly adhered to the surface of the fluorinated carbon by ultrasonic treatment to obtain a mixed solution. The mixed solution is subjected to solid-liquid separation, and the solid product is collected; The solid product was washed and dried to obtain a fullerol-modified fluorinated carbon composite material.

[0016] The method for preparing the fullerol-modified fluorinated carbon composite material, wherein the organic solvent is selected from any one or more combinations of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, anhydrous ethanol, methanol, isopropanol, and acetone.

[0017] The method for preparing the fullerol-modified fluorinated carbon composite material includes an ultrasonic power of 20-500W and an ultrasonic treatment time of 0.5-12h.

[0018] A positive electrode sheet, wherein the positive electrode sheet comprises the fullerol-modified fluorinated carbon composite material described in this invention.

[0019] The positive electrode sheet further includes a binder and a conductive agent. The mass ratio of the fullerol-modified fluorinated carbon composite material, the binder, and the conductive agent is (6-9.5):(0.5-2):(0.5-2). The binder is selected from any one or more combinations of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, and polytetrafluoroethylene. The conductive agent is selected from any one or more combinations of conductive carbon black, Ketjen black, acetylene black, carbon nanotubes, and graphene. The current collector of the positive electrode sheet is selected from any one of aluminum foil, nickel foil, carbon cloth, and stainless steel foil.

[0020] A primary lithium battery, wherein the primary lithium battery comprises the positive electrode sheet described in this invention.

[0021] Beneficial Effects: The fullerol-modified fluorinated carbon composite material provided by this invention, by introducing specific fullerol components and combining them with fluorinated carbon, allows the hydroxyl functional groups on the surface of the fullerol to be anchored to the surface of the fluorinated carbon through hydrogen bonding, achieving non-destructive surface modification of the fluorinated carbon particles. This modification process optimizes the stacking structure of the fluorinated carbon layers and broadens the interlayer ion transport channels. Simultaneously, the uniformly distributed fullerol can construct continuous electronic conduction pathways between the fluorinated carbon particles, thereby simultaneously improving the electronic conductivity and lithium-ion diffusion kinetics of the composite material. Therefore, when this composite material is used as the positive electrode of a lithium primary battery, it effectively alleviates the polarization phenomenon during high-rate discharge, enabling the battery to achieve significantly improved power density and rate performance while maintaining high energy density. Furthermore, the introduction of fullerol allows the composite material to be well-suited to various binder systems, such as aqueous or oil-based systems, which is beneficial for simplifying the preparation process and achieving green large-scale production. Attached Figure Description

[0022] Figure 1 A flowchart illustrating the preparation method of a fullerol-modified fluorinated carbon composite material provided by this invention.

[0023] Figure 2 This is a SEM image of the original fluorocarbon material.

[0024] Figure 3 This is a SEM image of the fullerol-modified fluorinated carbon composite material prepared in Example 1 of this invention.

[0025] Figure 4 This is a TEM image of the fullerol-modified fluorinated carbon composite material prepared in Example 1 of the present invention.

[0026] Figure 5 The diagram shows the discharge performance of the original fluorinated carbon cathode material.

[0027] Figure 6 The discharge performance diagram shows the positive electrode of the fullerol-modified fluorinated carbon composite material prepared in Example 1 of this invention.

[0028] Figure 7 Laguna diagrams of the original fluorinated carbon sample and the positive electrode of the fullerol-modified fluorinated carbon composite material of Example 1 of this invention.

[0029] Figure 8 The discharge performance diagram of the positive electrode of the fullerol-modified fluorinated carbon composite material in Example 2 of the present invention is shown. Detailed Implementation

[0030] This invention provides a method for preparing fullerol-modified fluorinated carbon composite materials and their application in lithium primary batteries. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0031] The present invention provides a fullerol-modified fluorinated carbon composite material, comprising fluorinated carbon and fullerol, wherein the fullerol is anchored to the surface of the fluorinated carbon through hydrogen bonding.

[0032] In this invention, fullerol refers to hydroxylated fullerene derivatives with a core structure of C60 carbon cages and a surface modified with hydroxyl functional groups (-OH); fluorinated carbon refers to compounds with carbon and fluorine as the main components, typically having a layered structure, and its general chemical formula can be represented as CF. x In this invention, hydrogen bonds are formed between the hydroxyl functional groups on the surface of fullerol and the fluorine atoms or oxygen-containing defect sites on the surface of fluorinated carbon particles through ultrasonic treatment and other methods, thereby tightly anchoring the fullerol molecules to the fluorinated carbon surface. Hydrogen bonding, as a non-covalent interaction, has a moderate bond energy (approximately 5-30 kJ / mol), sufficient to ensure stable adhesion of fullerol to the fluorinated carbon surface without disrupting the CF covalent bond structure of the fluorinated carbon. This is a typical non-destructive interface modification, fundamentally different from existing modification strategies such as chemical reduction and carbothermal reduction, which require the destruction of CF bonds. This non-destructive interface modification optimizes the stacking structure of the fluorinated carbon sheets and broadens the lithium-ion transport channels. Furthermore, the uniformly dispersed fullerol nanoparticles with good electron affinity construct a continuous electron conduction network between the fluorinated carbon particles, while their amphiphilic (hydrophilic / lipophilic) properties improve compatibility with different binder systems. The synergistic effect of the two essentially improves the electronic conductivity and lithium-ion diffusion kinetics of the composite material simultaneously, thereby solving the problem of poor high-rate performance of fluorinated carbon materials in primary lithium batteries.

[0033] In some embodiments, to maximize the retention of the high energy density advantage of the fluorinated carbon matrix while improving kinetic performance by introducing fullerols, the fullerol accounts for 0.1wt%-10wt% of the total mass of the fullerol-modified fluorinated carbon composite material. If too little fullerol is added (<0.1%), an effective continuous conductive network may not be constructed, resulting in limited modification effects; if too much is added (>10%), the fullerol may aggregate on the fluorinated carbon surface, thus hindering Li... + This creates diffusion channels and dilutes the content of the positive electrode active material, reducing the overall energy density. For example, setting the fullerol content to 2 wt% in the composite material can significantly reduce charge transfer resistance without significantly diluting the overall energy density of the material.

[0034] In some embodiments, considering the stability of the synthesis process and material costs, the fullerol with the molecular formula C60(OH) is used. n In this context, n is an integer from 16 to 40. When the number of hydroxyl groups is between 16 and 40, fullerols possess both good polarity and moderate molecular rigidity, enabling them to effectively anchor to the surface of fluorinated carbon via hydrogen bonds while maintaining the electron transport capability of the carbon cage. If the number of hydroxyl groups is too low (n < 16), the fullerol lacks sufficient polarity, making it difficult to form a stable dispersion in polar solvents, and there are insufficient hydrogen bond anchoring sites. If the number of hydroxyl groups is too high (n > 40), the fullerol molecule becomes too flexible, excessively weakening the electronic properties of the carbon cage, which is detrimental to the construction of a conductive network. In other words, the hydroxyl content of fullerols within this range is moderate, avoiding the problems of excessive hydrophilicity due to too many hydroxyl groups affecting its application in oily binder systems, or poor dispersibility and insufficient active sites due to too few hydroxyl groups. For example, fullerol with n = 24 exhibits excellent solubility and dispersion stability in N,N-dimethylformamide (DMF) / ethanol mixed solvents. Through the above settings, this invention improves the availability of materials and the versatility of processes while ensuring performance.

[0035] In some embodiments, the molecular formula of the fluorinated carbon is CF. x Where x = 0.5-1.2, the x value represents the degree of fluorination of the fluorinated carbon, which directly affects the theoretical specific capacity and electronic conductivity of the material. When the x value is too low (e.g., x = 0.5), the conductivity of the material improves but the theoretical capacity decreases; when the x value is too high (e.g., x = 1.2), the theoretical capacity is high but the conductivity is extremely poor, and the structural stability may decrease. Choosing this range allows for a balance between energy density and conductivity. To illustrate with a specific example, fluorinated graphite with x = 1.0 is selected as the base material, which has a high theoretical energy density, providing a good foundation for the modification in this invention.

[0036] In some embodiments, the fluorinated carbon includes any one or more combinations of fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, fluorinated carbon fibers, fluorinated Ketjen black, and fluorinated acetylene black, but is not limited thereto. Fluorinated carbons obtained after fluorination treatment of different carbon source precursors vary in morphology, specific surface area, fluorine content, etc., and can all be used as the matrix material of the present invention.

[0037] In some embodiments, the fullerol is distributed in the form of nanoparticles on the surface and subsurface region of the fluorinated carbon. The particle size of the fullerol nanoparticles is 1-100 nm, more preferably 5-50 nm, and most preferably 10-30 nm. The uniform distribution of fullerol in the form of nanoparticles on the fluorinated carbon surface, rather than forming a continuous thick coating layer, is a key feature that distinguishes this invention from traditional surface coating modification. The nanoparticle morphology has the following advantages: 1) Fullerol nanoparticles can form point-contact conductive bridges between fluorinated carbon particles, constructing a highly efficient electronic conductive network with a smaller amount of fullerol; 2) The gaps between particles allow the electrolyte and Li... + 3) Fullerols at the nanoscale have a higher specific surface area, which can provide more electrochemically active interfaces.

[0038] In this embodiment, the particle size of fullerol nanoparticles has a significant impact on the modification effect. When the particle size is <1 nm, fullerol may exist in the form of single molecules. Although the dispersion is uniform, the conductive bridging ability of a single molecule is limited. When the particle size is 5-50 nm, the fullerol nanoparticles have a moderate size and can effectively build conductive pathways between fluorinated carbon particles. When the particle size is 10-30 nm (the optimal range), the size of the fullerol nanoparticles matches the microstructure characteristics of fluorinated carbon best, resulting in the best modification effect. When the particle size is >100 nm, the fullerol particles are too large and difficult to distribute uniformly on the surface of fluorinated carbon. Furthermore, large particles may lead to discontinuities in the local conductive network.

[0039] In this embodiment, the subsurface of fluorinated carbon refers to the shallow region tens of nanometers below the surface layer of fluorinated carbon. During ultrasonic treatment, some fullerol nanoparticles may embed into the interlayer or shallow surface pores of fluorinated carbon, forming a subsurface distribution. This subsurface distribution makes the interfacial contact between fullerol and fluorinated carbon more compact, which is beneficial for interfacial charge transfer.

[0040] In some embodiments, a method for preparing fullerol-modified fluorinated carbon composite materials as described in this invention is also provided, such as... Figure 1 As shown, it includes the following steps: S10. Disperse fullerol in an organic solvent to form a fullerol dispersion; S20. Fluorocarbon powder is added to the fullerol dispersion, and the fullerol is uniformly adhered to the surface of the fluorocarbon by ultrasonic treatment to obtain a mixed solution. S30. Perform solid-liquid separation on the mixed solution and collect the solid product; S40. The solid product is washed and dried to obtain a fullerol-modified fluorinated carbon composite material.

[0041] The core of the preparation method provided in this embodiment lies in the liquid-phase ultrasound-assisted self-assembly strategy. Under the action of ultrasound, fullerol molecules / nano-aggregates in the fullerol dispersion gain sufficient kinetic energy to fully diffuse and adsorb onto the surface of fluorinated carbon. The cavitation effect of ultrasound can also promote the moderate peeling and dispersion of fluorinated carbon sheets, increasing the number of anchorable sites. The entire process does not require high temperature, high pressure, or highly corrosive reagents, is mild, and is easy to operate, showing good prospects for large-scale production. In this embodiment, the purpose of step S10 is to fully depolymerize and uniformly disperse the agglomerated fullerol particles, laying the foundation for subsequent uniform composite. Detailed dispersion can be achieved by mixing fullerol powder with an organic solvent at room temperature and stirring on a magnetic stirrer at 300-600 r / min for 0.5 to 2 hours until a uniform and stable dispersion is formed, free of visible particles or precipitates. Step S20 is crucial in the composite process. The cavitation effect and mechanical action of ultrasound promote the full movement of fullerol molecules in the liquid phase and their collision with fluorinated carbon particles. The hydroxyl groups on their surface are anchored to the defect sites or interlayers of the fluorinated carbon through hydrogen bonding. For example, detailed ultrasonic treatment can be performed for 1 to 6 hours in a water bath ultrasonic processor at a power of 40W-150W.

[0042] In steps S30-S40, the purpose of solid-liquid separation is to remove excess solvent and unadsorbed free fullerol; washing usually uses the same solvent as in step S10 (such as anhydrous ethanol) to remove residual impurities; drying is to completely remove the solvent and obtain a dry composite powder; the above process conditions directly affect the uniformity of fullerol modification and the bonding strength on the fluorinated carbon surface, thus determining the electrochemical performance of the final composite material.

[0043] In some embodiments, the organic solvent is selected from any one or more combinations of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, anhydrous ethanol, methanol, isopropanol, and acetone, but is not limited thereto. DMF exhibits excellent solubility / dispersion ability for fullerols, while anhydrous ethanol has the advantages of low toxicity and high volatility. For example, the solvent is a mixture of N,N-dimethylformamide and anhydrous ethanol, with a volume ratio of N,N-dimethylformamide to anhydrous ethanol of 1:0.5 to 1:2. For instance, using a DMF:ethanol volume ratio of 1:1 ensures sufficient dissolution of fullerols while lowering the overall solvent boiling point using ethanol, making subsequent washing steps (using ethanol) more compatible and efficient.

[0044] In some embodiments, the ultrasonic power of the ultrasonic treatment is 20-500W, and the ultrasonic treatment time is 0.5-12h. The ultrasonic power and time together determine the energy input into the system. Too low a power or too short a time may lead to incomplete recombination, meaning that fullerols cannot be effectively anchored to the fluorinated carbon surface; too high a power may cause localized overheating, potentially damaging the fullerol structure or even causing the adsorbed fullerols to detach, or leading to excessive peeling of the fluorinated carbon sheets. In a specific example, an ultrasonic power of 80 W and a treatment time of 3 hours were set, under which the recombination effect was significant and the material structure remained intact.

[0045] In some embodiments, a positive electrode sheet is also provided, the positive electrode sheet comprising the fullerol-modified fluorinated carbon composite material of the present invention, and further comprising a binder and a conductive agent, wherein the mass ratio of the fullerol-modified fluorinated carbon composite material, the binder and the conductive agent is (6-9.5):(0.5-2):(0.5-2); the current collector of the positive electrode sheet is selected from any one of aluminum foil, nickel foil, carbon cloth and stainless steel foil.

[0046] In this embodiment, the binder system is used to bond the active material particles and conductive agent into a film and attach it to the current collector; the addition of the conductive agent, in synergy with fullerol, further strengthens the overall electronic conductivity network of the electrode. The binder is selected from any one or more combinations of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, and polytetrafluoroethylene. Different binders are suitable for different solvent systems, imparting different flexibility and interfacial stability to the electrode. The conductive agent is selected from any one or more combinations of conductive carbon black, Ketjen black, acetylene black, carbon nanotubes, and graphene. These carbon-based conductive agents have high specific surface area and excellent conductivity, and can synergize with fullerol to build a more complete and efficient conductive network between fluorinated carbon particles, further reducing the ohmic resistance of the electrode.

[0047] In some embodiments, a primary lithium battery is also provided, the primary lithium battery comprising the positive electrode sheet described in this invention. Preferably, the negative electrode of the primary lithium battery is metallic lithium or a lithium alloy, and the electrolyte is an organic electrolyte containing a lithium salt. The lithium salt is selected from any one or more combinations of LiPF6, LiTFSI, and LiFSI, and the solvent of the organic electrolyte is selected from any one or more combinations of carbonates, ethers, and sulfones.

[0048] The present invention will be further explained and illustrated below through specific embodiments: Example 1 (PVDF oil system) This invention provides a method for preparing fullerol-modified fluorinated carbon composite materials and their application in lithium primary batteries. The method includes the following steps: Step 1: At room temperature, add 0.1g of fullerol (C60(OH)). 18 The sample, 50 mL of N,N-dimethylformamide solution (DMF) and 50 mL of anhydrous ethanol were mixed and stirred in a magnetic stirrer at 400 r / min for 30 min to form a uniform dispersion. Step 2: Add 9.9 g of fluorinated carbon powder (fluorinated graphite, CF3) to the dispersion obtained in Step 1. 1.0 The sample was placed in a water bath ultrasonic bath and ultrasonically treated for 3 hours at 80 W power. Step 3: Centrifuge the sample obtained in Step 2 at 8000 r / min for 10 min to obtain a solid. Step 4: Wash the sample obtained in Step 3 three times by centrifugation with anhydrous ethanol; Step 5: Place the sample obtained in Step 4 into a vacuum drying oven and dry it at 70°C for 12 h to obtain fullerol-modified fluorinated carbon composite material (fullerol mass percentage approximately 1 wt%).

[0049] Step 6: Mix the obtained fullerol-modified fluorinated carbon composite material with PVDF binder and Super P conductive agent at a mass ratio of 8:1:1, add an appropriate amount of NMP solvent and stir evenly, coat it on aluminum foil (coating thickness 180 μm), and obtain the positive electrode sheet after drying, rolling and cutting.

[0050] Step 7: Assemble CR2032 coin cells in an argon glove box using lithium metal sheets as the negative electrode, Celgard 2400 as the separator, and 1 M LiBF4 / PC+DME (volume ratio 1:1) as the electrolyte.

[0051] Performance testing and results analysis: Figure 2 and Figure 3SEM images of the surface morphology of the original fluorinated carbon material and the fullerol-modified fluorinated carbon composite material prepared in Example 1 are shown. As can be seen from the images, the unmodified original fluorinated carbon sheets exhibit disordered particle stacking, with tight packing between sheets, narrow interlayer pores, smooth particle surfaces, and a lack of conductive pathways. However, after ultrasonic interface modification with fullerol, the stacking state of the fluorinated carbon sheets is significantly optimized, the interlayer gaps are moderately widened, and the stacking order is improved. Fullerol is uniformly adhered to the surface of the fluorinated carbon sheets, without large-area agglomeration or obvious blocky impurities. This indicates that the modification method of this invention is a non-destructive surface modification that does not damage the original crystalline framework structure of the fluorinated carbon sheets. Fullerol modification can effectively control the stacking mode of fluorinated carbon sheets, broaden lithium-ion transport channels, and simultaneously build a continuous conductive network between particles based on the uniformly distributed fullerol, which is beneficial for improving electron conduction and Li-ion conductivity. + Diffusion kinetics performance.

[0052] Figure 4 A TEM image of the fullerol-modified fluorinated carbon composite material prepared in Example 1 is shown. (C60(OH)) 18 Distributed in CF in the form of nanoparticles x Surface and subsurface regions. C60(OH) 18 The surface of amorphous fluorinated carbon was modified by forming a heterogeneous coating embedded with short-range carbon layers. This was achieved through C60(OH)... 18 -CF x The composite interface introduces active sites and buffer structures, and this modified layer provides crucial structural support, contributing to improved CF. x Electrochemical performance of cathode materials.

[0053] pass Figure 5 (Original fluorinated carbon) and Figure 6 The discharge performance comparison of the modified sample in Example 1 shows that the discharge rate of the modified lithium / carbon fluoride battery increased from a maximum of 10 C to 20 C, and the discharge plateau became more stable. The original carbon fluoride battery showed a significant tilt and voltage drop at a discharge rate of 10 C, while the modified sample maintained a relatively stable discharge plateau at a discharge rate of 20 C.

[0054] Depend on Figure 7As shown in the Lagrangian plot, at a low discharge rate of 0.01 C, the energy densities of the two cathode materials before and after modification are similar (both close to the theoretical value). With increasing discharge rate and power density, the energy density of the original fluorinated carbon cathode exhibits a precipitous decline; while the energy density decay rate of the modified composite cathode in Example 1 is significantly slowed, maintaining considerable energy output even at a high discharge rate of 20 C and ultra-high power density. These results confirm that fluorinated carbon materials modified at the fullerol interface can significantly improve high-rate discharge kinetics, effectively alleviate polarization losses under high current, and simultaneously achieve both high energy density and high power density. Specifically, at a 10 C rate, the modified sample shows an approximately 60% increase in energy density and an approximately 75% reduction in charge transfer resistance compared to the original sample.

[0055] Example 2 (CMC water system) The difference between this embodiment and Embodiment 1 is that CMC is used as the binder and deionized water is used as the solvent, while the remaining steps are the same as in Embodiment 1.

[0056] Steps one through five are the same as in Example 1.

[0057] Step 6: Mix the obtained fullerol-modified fluorinated carbon composite material with CMC binder and Super P conductive agent at a mass ratio of 8:1:1, add an appropriate amount of deionized water and stir evenly, coat it on aluminum foil, and then dry, roll and cut it to obtain the positive electrode sheet.

[0058] Step seven is the same as in Example 1.

[0059] Performance testing and results analysis: Figure 8 The discharge performance of the fullerol-modified fluorinated carbon composite cathode prepared in Example 2 at different rates is demonstrated. The results show that at high rates (>7 C), the discharge plateau of the fullerol-modified fluorinated carbon composite cathode remains stable, and the capacity retention is excellent.

[0060] The above results show that the fullerol-modified fluorinated carbon composite material of the present invention has good compatibility with the CMC aqueous binder system. The electrode prepared by the aqueous slurry process still has excellent electron conduction and lithium-ion diffusion kinetics, and can simultaneously take into account high specific capacity and wide discharge capability. It avoids the defects of high toxicity and high cost of organic solvents in traditional PVDF oil-based binders, and is more conducive to green and large-scale production.

[0061] Example 3 (Comparison of different fullerol contents) The difference between this embodiment and Example 1 is that the dosage of fullerol is set to 0.01 g, 0.05 g, 0.1 g, 0.2 g, 0.3 g, 0.5 g, 0.8 g, and 1.0 g (the amount of fluorinated carbon is changed accordingly so that the total mass of fullerol and fluorinated carbon is fixed at 10 g), corresponding to theoretical fullerol mass percentages of 0.1 wt%, 0.5 wt%, 1 wt%, 2 wt%, 3 wt%, 5 wt%, 8 wt%, and 10 wt%, respectively. The remaining steps are the same as in Example 1.

[0062] Performance testing and results analysis: The electrochemical performance of each sample was tested, and the results are shown in Table 1.

[0063] Table 1 Performance Test Results

[0064] As can be seen from the results in Table 1, when the amount of fullerol added is <0.5 wt%, the fullerol coverage density on the surface of fluorinated carbon is insufficient, making it difficult to form a continuous electronic conductive network. Electrochemical tests showed that at 10 C rate, the energy density of the sample with an addition of 0.1 wt% only increased by about 15%, which was not significant. When the addition of fullerol was 0.5-1 wt%, fullerol began to form a relatively continuous nanoparticle coverage on the fluorinated carbon surface, and a conductive network was initially formed, resulting in an energy density increase of about 30%-50% at 10 C rate. When the addition of fullerol was 1-3 wt% (the optimal range), fullerol formed a uniform and continuous nanoparticle distribution on the fluorinated carbon surface, and both the electronic conductivity network and ion diffusion channels reached their optimal state, resulting in an energy density increase of over 60% at 10 C rate and a charge transfer resistance reduction of up to 75%. When the addition of fullerol was 3-5 wt%, the fullerol coverage tended to saturate, and the performance improvement brought by further increasing the addition amount tended to plateau, with some samples even showing a slight decrease (because excessive fullerol began to block Li). + (Channel); When the amount of fullerol added is >5 wt%, fullerol undergoes significant aggregation on the surface of fluorinated carbon, forming a locally thick coating layer, which severely hinders Li (channel). + The diffusion of inactive substances (fullerols) was also a factor. At the same time, the high proportion of inactive substances diluted the content of active substances, leading to a decrease in overall energy density.

[0065] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A fullerol-modified fluorinated carbon composite material, characterized in that, It includes fluorinated carbon and fullerol, wherein the fullerol is anchored to the surface of the fluorinated carbon via hydrogen bonding.

2. The fullerol-modified fluorinated carbon composite material according to claim 1, characterized in that, The fullerol accounts for 0.1wt%-10wt% of the total mass of the fullerol-modified fluorinated carbon composite material.

3. The fullerol-modified fluorinated carbon composite material according to claim 1, characterized in that, The fluorinated carbon includes any one or more combinations of fluorinated graphite, fluorinated graphene, fluorinated carbon nanotubes, fluorinated carbon fibers, fluorinated Ketjen black, and fluorinated acetylene black.

4. The fullerol-modified fluorinated carbon composite material according to claim 1, characterized in that, The fullerol has the molecular formula C60(OH). n Where n is an integer from 16 to 40; the molecular formula of the fluorinated carbon is CF. x , where x = 0.5 - 1.

2.

5. A method for preparing the fullerol-modified fluorinated carbon composite material as described in any one of claims 1-4, characterized in that, Including the following steps: Fullerol is dispersed in an organic solvent to form a fullerol dispersion; Fluorinated carbon powder is added to the fullerol dispersion, and the fullerol is uniformly adhered to the surface of the fluorinated carbon by ultrasonic treatment to obtain a mixed solution. The mixed solution is subjected to solid-liquid separation, and the solid product is collected; The solid product was washed and dried to obtain a fullerol-modified fluorinated carbon composite material.

6. The method for preparing the fullerol-modified fluorinated carbon composite material according to claim 5, characterized in that, The organic solvent is selected from any one or a combination of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, anhydrous ethanol, methanol, isopropanol, and acetone.

7. The method for preparing the fullerol-modified fluorinated carbon composite material according to claim 5, characterized in that, The ultrasonic power of the ultrasonic treatment is 20-500W, and the ultrasonic treatment time is 0.5-12h.

8. A positive electrode sheet, characterized in that, The positive electrode comprises the fullerol-modified fluorinated carbon composite material as described in any one of claims 1-4.

9. The positive electrode sheet according to claim 8, characterized in that, The positive electrode sheet further includes a binder and a conductive agent. The mass ratio of the fullerol-modified fluorinated carbon composite material, the binder, and the conductive agent is (6-9.5):(0.5-2):(0.5-2). The binder is selected from any one or more combinations of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, and polytetrafluoroethylene. The conductive agent is selected from any one or more combinations of conductive carbon black, Ketjen black, acetylene black, carbon nanotubes, and graphene. The current collector of the positive electrode sheet is selected from any one of aluminum foil, nickel foil, carbon cloth, and stainless steel foil.

10. A primary lithium battery, characterized in that, The primary lithium battery comprises the positive electrode sheet as described in claim 8 or 9.